Effect of assisted hatching on pregnancy outcomes: a systematic review and meta-analysis of randomized controlled trials - Da Li; Dalei Yang; Jing An; Jiao Jiao; Yiming Zhou; Qi‐Jun Wu; Xiuxia Wang (2016)
Abstract Emerging evidence suggests that assisted hatching (AH) techniques may improve clinical pregnancy rates, particularly in poor prognosis patients; however, there still remains considerable uncertainty. We conducted a meta-analysis to verify the effect of AH on pregnancy outcomes. We searched for related studies published in PubMed, Web of Science and Cochrane library databases from start dates to October 10, 2015. Totally, 36 randomized controlled trials with 6459 participants were included. Summary odds ratios (ORs) with 95% confidence intervals (CIs) for whether by AH or not were estimated. We found a significant increase in clinical pregnancy (OR = 1.16, 95% CI = 1.00–1.36, I 2 = 48.3%) and multiple pregnancy rates (OR = 1.50, 95% CI = 1.11–2.01, I 2 = 44.0%) with AH when compared to the control. Numerous subgroup analyses stratified by hatching method, conception mode, extent of AH, embryos transfer status and previous failure history were also carried out. Interestingly, significant results of clinical pregnancy as well as multiple pregnancy rates were observed among women who received intracytoplasmic sperm injection and who received AH which the zona were completely removed. In summary, this meta-analysis supports that AH was associated with an increased chance of achieving clinical pregnancy and multiple pregnancy. Whether AH significantly changes live birth and miscarriage rates needs further investigations.